PENDAMPINGAN USAHA TEH CELUP MENGKUDU PADA UD MAJU JAYA DESA LONGOS KECAMATAN GAPURA - Ismawati Ismawati; Ratih Yuniastri; R. Amalia Destryana (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2019)
UD Maju Jaya is one of the businesses of processing and marketing of noni processed products. UD Maju Jaya processes noni into dried noni products. But in the course of its business, UD Maju Jaya wants the development of Noni products to become a beverage product that has appeal. However, partners do not have the skills and production facilities are still limited. Based on the problems faced by partners, the team provided assistance through training activities and the provision of production equipment in the form of miller units, packaging, tea bags and label of packaging. The results of the mentoring activities are that the partners have produced and developed Noni tea bags directly by being placed in stores and online market by Facebook